2019
DOI: 10.3389/fendo.2019.00887
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Analogs Reduce Stress and Inflammation Indices in Experimental Models of Diabetes

Abstract: Chronic inflammation and oxidative stress lead to a multitude of adverse cellular responses in target organs of chronic diabetic complications. Curcumin, a highly investigated phytochemical, has been shown to exhibit both anti-inflammatory and antioxidant activities. However, the clinical application of curcumin has been greatly limited due to a poor pharmacokinetic profile. To overcome these limitations, we have generated analogs of curcumin to enhance bioavailability and offer a preferable pharmacokinetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…However, other human studies have shown that single lifestyle factor changes, such as physical activity changes, have less effect on cognitive function in neurodegenerative diseases. Curcumin is a well-known natural antioxidant that reduces the inflammatory response in diabetes via Nrf2 and PI3K/AKT signaling pathways [27][28][29][30][31]. Evidence indicates that curcumin can ameliorate pathologies associated to amyloid-β and recover p-Tau-related pathologies in animal models [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…However, other human studies have shown that single lifestyle factor changes, such as physical activity changes, have less effect on cognitive function in neurodegenerative diseases. Curcumin is a well-known natural antioxidant that reduces the inflammatory response in diabetes via Nrf2 and PI3K/AKT signaling pathways [27][28][29][30][31]. Evidence indicates that curcumin can ameliorate pathologies associated to amyloid-β and recover p-Tau-related pathologies in animal models [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, it was found that curcumin presents powerful anti-inflammatory and anti-oxidant activities. It stabilizes the levels of interleukin 6 (IL-6), tumor necrosis factor α (TNF-α), ECM proteins (fibronectin and collagen), as well as a vascular endothelial growth factor (VEGF) [124].…”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin is a polyphenol and natural product isolated from root of turmeric rhizome [ 179 , 180 , 181 ]. It has pharmacological activities for the amelioration of cardiovascular disorders [ 182 ], improving blood lipids [ 183 ], reducing the risk of diabetes development [ 184 , 185 ], and so on. However, among them, antitumor activity of curcumin is of importance, since curcumin has been able to suppress proliferation of cancer cells, induce apoptosis, and inhibit their migration [ 167 , 186 , 187 ].…”
Section: Antitumor Compounds Target Ptenmentioning
confidence: 99%